KATA SIFAT BAHASA INGGRIS DALAM JURNAL ENGLISH TEACHING FORUM - RUMOKOY, TRISNO RIANDY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTS This study entitled â€œEnglish Adjective in Journal English Teaching Forumâ€, is aimed at identifying , classifying and analizing English Adjetiveâ€Ÿs found in the Journal. The data have been collected by reading all the pages from that Journal and analized them based on Harmanâ€Ÿs concept. The research questions are : What are the forms of adjectives are found in Journal English Teaching Forum? What are the functions of adjectives are foundÂ  in Journal English Teaching Forum? Objective of the research : To identify and classify the form of adjectives found in Journal English Teaching Forum and To analyse the function of adjectives found in journal English Teaching Forum. The result found in the journal : In terms of descriptive adjective the writer found, five forms, of descriptive adjectives those are quality adjective, quantity adjective, compound adjectives, color adjective and size adjectives. In terms of definitive adjectives, there are two forms. In termsof function, adjective can be formed as attributive and predicative. Both ofÂ  them arefound in journal Teaching English Forum this Journal. Â Key Words : English adjective, grammatical analysis, Journal : English Teaching Forum.